(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Road transportation infrastructure is fundamental to regional mobility, economic growth, and urban development. However, increasing traffic demand within rapidly urbanizing cities often exceeds the carrying capacity of existing road networks, resulting in chronic congestion, travel delays, increased transportation costs, and reduced operational efficiency. The construction of the Atani–Obosi Access Route of the Second Niger Bridge was undertaken to improve regional accessibility and redistribute vehicular traffic previously concentrated along the existing Niger Bridge corridor into Onitsha. This study evaluated variations in traffic load resulting from the construction of the access route by comparing traffic conditions before the project with current traffic flow patterns into Onitsha. The study adopted a transportation assessment approach integrating Geographic Information Systems (GIS), field traffic observations, and statistical analysis to evaluate traffic redistribution associated with the new transportation corridor. Traffic volume datasets obtained during the study were analysed to determine changes in traffic intensity, spatial distribution of vehicular movement, and transportation efficiency before and after construction of the access route. Comparative analyses were undertaken to determine the extent to which the new corridor influenced vehicular movement into Onitsha and surrounding communities. The findings indicate that the Atani–Obosi Access Route has significantly altered traffic distribution within the study area by providing an alternative transportation corridor that reduced dependence on the traditional route into Onitsha. Traffic flow became more spatially distributed, thereby reducing traffic pressure along previously congested sections of the existing road network. The study further demonstrates that the access route has improved regional accessibility, enhanced transportation efficiency, and strengthened interconnectivity between communities within Anambra State and neighbouring regions. The study concludes that the Atani–Obosi Access Route has contributed significantly to traffic redistribution and improved transportation performance within the study area. It recommends the integration of continuous traffic monitoring, intelligent transportation planning, and evidence-based infrastructure management into future highway development projects to ensure sustainable transportation systems.